Group Guidance with Sociodrama Technique Containing The Values of Catur Piwulang Sunan Drajat to Develop Students' Altruistic Attitudes - Arianti, Alivia Eka; Hambali, IM; Hidayatur Rahman, Diniy (Psikopedagogia, 2024)
This research and development project aims to produce group guidance guidelines utilizing sociodrama techniques, incorporating Sunan Drajat chess scores that are deemed feasible by experts and proven effective in fostering the altruistic attitudes of high school students. This product was developed in accordance with the ADDIE model of research and development, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research and development involved eight students from class X at SMA Negeri 1 Sukodadi, along with counselors and guidance and counseling experts. The instruments used in this study include altruistic attitude scales and assessment questionnaires for experts and potential users. The product validity test was conducted through assessments by material experts, media experts, cultural experts, and potential users, utilizing inter-rater agreement analysis. Furthermore, to determine the effectiveness of the product, the Wilcoxon signed-rank test was employed. Based on the results of the data analysis, the developed guidelines demonstrate very high validity in terms of acceptability, which includes accuracy, usability, convenience, and attractiveness. The results of the effectiveness test indicated that the intervention conducted by the counselor was effective in developing the altruistic attitudes of high school students. The findings of this research and development are recommended for implementation in group guidance services as one of the intervention strategies that can enhance students' altruistic attitudes.